2022
DOI: 10.3389/fnut.2022.730841
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary and Lifestyle Inflammation Score With Cardiorespiratory Fitness

Abstract: ObjectiveWe aimed to assess the potential association of dietary (DIS) and lifestyle inflammation score (LIS) and their joint association (DLIS) with cardiorespiratory fitness (CRF) in Tehranian adults.DesignThe present study was designed cross-sectional.ParticipantsA total of 265 males and females aged 18–70 years (mean ± SD: 36.9 ± 13.3) were entered in the present cross-sectional study. Eligible participants were healthy men and women who were free of medications and had no acute or chronic infection or inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…For everyone in the sample, the factor loading of each food group was multiplied by the mean consumption of each food group (in grams per day) to calculate factor scores for each dietary pattern. Adherence to dietary pattern was determined by splitting individual factor scores into quartiles, consistent with previous studies 20 30 31. For example, for a given dietary pattern, participants with a factor score in the top 25% were categorised as high adherers, whereas individuals with a factor score in the lowest 25% were categorised as low adherers 20 30 31.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For everyone in the sample, the factor loading of each food group was multiplied by the mean consumption of each food group (in grams per day) to calculate factor scores for each dietary pattern. Adherence to dietary pattern was determined by splitting individual factor scores into quartiles, consistent with previous studies 20 30 31. For example, for a given dietary pattern, participants with a factor score in the top 25% were categorised as high adherers, whereas individuals with a factor score in the lowest 25% were categorised as low adherers 20 30 31.…”
Section: Methodsmentioning
confidence: 99%
“…Adherence to dietary pattern was determined by splitting individual factor scores into quartiles, consistent with previous studies 20 30 31. For example, for a given dietary pattern, participants with a factor score in the top 25% were categorised as high adherers, whereas individuals with a factor score in the lowest 25% were categorised as low adherers 20 30 31. The adherence of a participant to any given dietary pattern did not preclude the participant from being a high or low adherer to any other dietary pattern.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that oxidative stress and inflammation can disturb physical fitness [ 11 , 12 ]. They can induce tissue injury leading to the poor function of tissues, resulting in reductions in cardiorespiratory fitness, range of motion, particularly around the joints, or flexibility, muscle strength, and endurance; thus, the applications of substances possessing antioxidant and anti-inflammatory effects, such as herbal extracts, as the functional ingredients for developing functional drinks have been the main area of focus.…”
Section: Introductionmentioning
confidence: 99%